Market competition in banking and asset-liability maturity mismatch of non-financial firms: Evidence from Vietnam - Thi Minh Hue Phan; Japan Huynh (PLoS ONE, 2026)
This study examines the effect of bank competition on corporate investment-financing maturity mismatch, utilizing a panel dataset of 498 listed firms in Vietnam from 2008 to 2024. Bank competition is measured using both structural and non-structural indicators, allowing for a nuanced assessment of market dynamics. The findings reveal a robust positive association between bank competition and maturity mismatch, suggesting that intensified competition leads firms to increase their reliance on short-term debt relative to long-term investment needs. This relationship holds under multiple robustness checks, including alternative variable constructions, fixed effects specifications, crisis period exclusions, and instrumental variable approaches. Mechanism analyses indicate that bank competition affects firms’ debt maturity structures, increasing both the proportion and scale of short-term borrowing. Heterogeneity tests further show that this effect is stronger among firms with higher bank debt dependence, greater financial constraints, and higher borrowing costs, while it is weaker in capital-intensive sectors.